MENTAL ACCOUNTING, ILUSI KEBAHAGIAN PADA KONSUMEN NOMOR BUNTUT ATAU TOGEL - vioneta cattravelly pandji; Bambang Minarso (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
This research aims to examine the effect of Mental Accounting Theory on the Illusion of Happiness, by providing evidence of a relationship between shopping behavior and fulfillment of happiness as described in the Illusionary Happiness Concept. This research was conducted in the Togel Semarang community using a questionnaire instrument which was processed using Regression Analysis, to Test Hypotheses